Developing Scientific Competence: Technologies, Tools, and Prospects - Kramarenko, Iryna (Educological discourse, 2025)
The article presents the theoretical foundations and empirical results of a study aimed at developing scientific competence among lower secondary school students. It substantiates the importance of updating learning tools in the context of educational digitalization, emphasizing the combination of traditional and modern instruments to ensure a comprehensive development of students’ knowledge, skills, and motivation. A comparative analysis of the effectiveness of traditional (printed textbooks, model-based lab activities) and modern digital tools (AR/VR, mobile applications, video lessons, simulations, gamified platforms) is provided based on six components of scientific competence: theoretical knowledge, conceptual visualization, research skills, digital literacy, motivation, and autonomy. The study methodology included a mixed-method approach that combined quantitative and qualitative methods, such as pedagogical experiments, surveys, testing, observations, and semi-structured interviews. The results indicate a significant advantage of digital tools in developing research skills, fostering critical thinking, and enhancing student engagement, while traditional tools remain effective for structuring and consolidating core knowledge. The experiment confirmed that the most effective educational outcomes are achieved through an integrated use of both digital and traditional tools. The scientific novelty of the study lies in the systematisation of learning tools by components of competence and the correlation of empirical results with the theoretical frameworks of Robert Gagné, Richard Mayer, John S. Brown, and Paul Duguid, regarding the cognitive and social nature of learning. Future research directions include an indepth analysis of the impact of specific digital technologies on the development of scientific competencies, adaptation of tools to blended and distance learning environments, and the design of innovative STEM-methodologies that incorporate inclusivity and interdisciplinarity.